NIR light-induced rapid self-healing hydrogel toward multifunctional applications in sensing. (March 2023) - Xu, Lijian; Chen, Yin; Yu, Maolin; Hou, Mengjuan; Gong, Guo; Tan, Haihu; Li, Na; Xu, Jianxiong
Abstract: Flexible conductive hydrogels with self-healing ability have attracted great attention in the fields of wearable devices and healthcare monitoring due to their recoverability and sustainability. Herein, the application of inorganic antimony sulfide (Sb2 S3 ) as photothermal agent is extended to the field of self-healing hydrogel for the first time. A near-infrared (NIR) light-induced rapid self-healing double-network conductive hydrogel (SPOH gel) via on-demand irradiation was fabricated by incorporating dopamine (DA)-modified polypyrrole (PPy) coated Sb2 S3 nanorod (Sb2 S3 @PPy-DA) into the polymer matrix of polyvinyl alcohol (PVA)/poly(N-(2-hydroxyethyl)acrylamide) (pHEAA) in a water-glycerol dispersion medium. The SPOH gel with adhesive and anti-freezing properties exhibited robust tensile strength (1.25 MPa), large elongation (620%), high interfacial toughness (251 J/m 2 ), and outstanding sensitivity (GF = 4.97). The incorporation of Sb2 S3 @PPy-DA for SPOH gel endowed high conductivity (2.26 S/m) and promoted rapid self-healing process under NIR light irradiation (within 90 s). Moreover, SPOH gel could be widely applied to various applications, including monitoring various human motions as strain sensor, detecting electrocardiogram signals as biopotential electrodes, and harvesting energy as self-powered device. The multifunctional SPOH gel with the integrated attractive capabilities of rapid self-reparability and real-time physiological signal detection, providing a promising route to develop wearable smart devices in motion monitoring, healthcare management, and energy harvesting applications. Graphical Abstract: ga1 Highlights: SPOH gel exhibited robust tensile strength and high conductivity by incorporation of Sb2 S3 @PPy-DA. The sample showed self-healing efficiency up to 100% upon NIR light irradiation for 90 s The gel was widely applied for monitoring various human motions, detecting electrocardiogram signals, and harvesting energy.